Neurotrophic, Cytoprotective, and Anti-inflammatory Effects of St. John's Wort Extract on Differentiated Mouse Hippocampal HT-22 Neurons - Bonaterra, Gabriel A.; Schwendler, Anna; Hüther, Julian; Schwarzbach, Hans; Schwarz, Anja; Kolb, Christiane; Abdel-Aziz, Heba; Kinscherf, Ralf (Frontiers in Pharmacology, 2018)
Introduction: Since ancient times Hypericum perforatum L. named St. John's wort (SJW), has been used in the management of a wide range of applications, including nervous disorders. Development of mood disorders are due to alterations in glutamate metabolism, initiation of inflammatory pathways, and changes of the neuronal plasticity. Previous studies suggest that the glutamatergic system contributes to the pathophysiology of depression. Extracts of SJW have been recommended for the treatment of depression. The aim of the present in vitro study was to evaluate the action of STW3-VI, a special SJW extract in differentiated mouse hippocampal HT-22 neurons. We evaluated the stimulation of neurogenesis, the protective effect against glutamate or N-methyl-D-aspartate receptor induced-excitotoxicity and its anti-inflammatory properties in LPS-activated human macrophages. Results: After 48 h treatment, STW3-VI stimulated the neurite formation by 25% in comparison with the control and showed protective effects against glutamate- or NMDA-induced cytotoxicity by significantly increasing the viability about +25 % or +50 %. In conjunction with these effects, after pretreatment with STW3-VI, the intracellular reduced glutathione content was significantly 2.3-fold increased compared with the neurons incubated with glutamate alone. Additionally, pre-treatment of human macrophages with STW3-VI showed anti-inflammatory effects after 24 h or 48 h concerning inhibition of LPS-induced TNF release by -47.3 % and -53.8 % (24h) or -25.0 % to -64.8 % (48h). Conclusions: Our data provide new evidence that STW3-VI protects hippocampal cells from NMDA- or glutamate-induced cytotoxicity. Moreover, our results indicate a morphological remodelling by increasing neurite outgrowth and activation of the anti-inflammatory defense by inhibition of the cytokine production in human macrophages after STW3-VI treatment. These protective, neurotrophic and anti-inflammatory properties may be beneficial in the treatment of depressive disorders.